Handbook of spatial statistics - Gelfand, Alan E., 1945-; Diggle, Peter J.; Fuentes, Montserrat; Guttorpt, Peter (Chapman & Hall/CRC handbooks of modern statistical methods., 2010)
"Assembling a collection of very prominent researchers in the field, the Handbook of Spatial Statistics presents a comprehensive treatment of both classical and state-of-the-art aspects of this maturing area. It takes a unified, integrated approach to the material, providing cross-references among chapters." "The handbook begins with a historical introduction detailing the evolution of the field. It then focuses on the three main branches of spatial statistics: continuous spatial variation (point referenced data); discrete spatial variation, including lattice and areal unit data; and spatial point patterns. The book also contains a section on space-time work as well as a section on important topics that build upon earlier chapters." "By collecting the major work in the field in one source, along with including an extensive bibliography, this handbook will assist future research efforts. It deftly balances theory and application, strongly emphasizes modeling, and introduces many real data analysis examples."--Jacket.